Effect of storage conditions on the postharvest quality changes of fresh mango fruits for export during transportation - Eriko Yasunaga (2018)
This study investigated the effects of the storage conditions, namely temperature and relative humidity on the quality of fresh mango fruit (Mangifera indica L. ‘Nam Dokmai’) before and after distribution from Thailand to Japan. Fruit samples were harvested from two commercial orchards in Phrao and Phitsanulok, Thailand, and stored immediately after harvest and after distribution for 46 d respectively at 15, 25 and 35°C. The contents of L-ascorbic acid (L-AsA), sugar components and total soluble solids (TSS), as well as hardness score and peel colour of fruit samples were measured as a fruit quality indicator. As a result, fruit samples from Pitsanulok attained a better storage condition sooner than Phrao samples because of shorter distance to the packing house in Bangkok. Despite of the similar hardness score, the total sugar contents and L-AsA contents at harvest was significantly higher for Phrao than Phitsanulok. Total sugar contents and TSS in the after-harvest experiment indicated postharvest ripening for which the storage temperature of 25°C was found to be optimal. In the after-distribution experiment, fruit quality parameters showed temperature-dependent responses of mango fruit. Further study is needed for an improved export system considering actual storage temperature of fresh mango fruit.